Determinación de microalbuminuria mediante la relación albúmina/creatinina en pacientes con diabetes mellitus tipo 2 (2007)
This research was carried out to establish the importance of glycolated hemoglobin (HbA1C), glycemia and the evolution time of diabetes mellitus (DM) type 2 in the determination of microalbuminuria as prediction factor of incipient renal nephropathy through the use of the albumin/creatinin ratio. Thirty patients of both sexes with controlled and uncontrolled DM type 2, as well as 30 healthy individuals, of similar age and sex proportion, were tested. Both groups were submitted during three weeks at three different moments to blood tests of basal glycemia and glycolated hemoglobin and microalbu-minura in punctual urine. The methods used for the evaluation were glycemia (Trinder), HbA1C (Craine JE), creatinin (Benedict-Behre) and albumin (immunoturbi-dimetria). Statistical analysis revealed a direct correlation between microalbuminuria, glycemia, glycolated hemo-globin and disease evolution time in both controlled and uncontrolled patients, with a mayor level of significance in the latter group. Within the progress of diabetes nephropathy, measured in terms of microalbuminuria, glycemia, glycolated hemoglobin and disease evolution time, their close relationship was made evident, which makes these factors susceptible to be clinically controlled in favor of DM type 2 patients. From the experimental and statistical point of view microalbuminuria, glycemic control and the disease evolution time are indicators of incipient renal nephropathy.